Intergenerational income and educational mobility in urban Chile - Javier Nú\~nez; Leslie Miranda (Estudios de Economía, 2011)
This paper provides evidence on the degree and patterns of intergenerational income and educational mobility in urban Chile. We find intergenerational income elasticities for Greater Santiago in Chile in the range of 0.52 to 0.54. This is lower than recent nation-wide elasticities for Chile of about 0.6-0.7, but still stands as fairly high in comparison with the comparable international evidence. We also find that intergenerational educational mobility is lower for the younger cohorts, which however does not necessarily imply an increase of intergenerational educational mobility in the last decades, as life-cycle effects may be at work. Finally, we find evidence of a higher degree of intergenerational persistence of income at the two extremes of the income distribution, which is more accentuated at the top centiles of the distribution. We suggest that this may mirror the unusually high concentration of income at the top of the income distribution in Chile, a hypothesis that requires further research.
Keywords: D3; I2; J6; 330; intergenerational mobility; schooling; mobility patterns; Einkommen; Soziale Mobilität; Intergenerational Mobility; Stadt; Chile